The psychosocial assessment of patients discharged from accident and emergency departments after deliberate self-poisoning. - Ebbage, J (1994)
One-third of accident and emergency (A & E) patients who deliberately take an overdose are not admitted to hospital, and this proportion is increasing. We conducted an audit of 300 case records of such patients from two different district health authorities in London. We found that only 4% of patients were assessed in the manner recommended by the Department of Health and 10% had no psychosocial assessment whatsoever. We recommend specific training, an assessment form, regular audit, and communication with the general practitioner.